Investigating the Components of Effective Management of Attention Seeking among Married Women from the Perspective of Family Counselors: Presenting a Treatment Model in a Qualitative Study - Khodaee , Sare; Yousefi , Zahra; khayatan , floor (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Nowadays, attention seeking has become a matter of concern in the family context and the need for prevention and adjustment is felt as a therapeutic necessity. Therefore, the present study aimed to investigate the components of effective management of attention seeking among married women from the perspective of family counselors and to present a treatment model. Methods: From experienced counselors who had the necessary experience in the field of family therapy, using purposive sampling method, 8 people were selected to participate in the study and were interviewed. The study method was reflective theme analysis. The interview tool was a semi-structured interview. Results: Data were analyzed by Clark and Brown method in six steps. The results of the analysis of the interviews showed that attention management is one of the three main categories of evaluation (with three organizing categories: self-report evaluation, evaluating symptoms with the help of interviews, and evaluating the individual and couple effects of attention seeking); 2) Individual therapy (with the organizing categories: insight, modifying cognitive stimulus cognitions, modifying attention-seeking behaviors and emotions) and couple therapy)with organizing categories: improving attachment, improving self-differentiation, and improving Life story) is composed. Conclusion: According to the results of a three-dimensional treatment model of evaluation, individual and couple therapy was formed, which can be helpful and inspiring counselors interested in this field.